International asset allocation: A new perspective - Lioui, Abraham; Poncet, Patrice (Journal of Banking & Finance, 2003)
We consider an international economy where the purchasing power parity (PPP) is violated and financial asset returns and exchange rates follow, in real terms, general diffusion processes driven by K state variables. A country-specific representative individual trades on available assets to maximize the expected utility of her final consumption. Her optimal strategy is shown to contain, in addition to the usual speculative component, only two hedging components, however large is K. The first one is associated with domestic interest rate risk and the second one with the risk brought about by the co-movements of the interest rates and the market prices of risk. The implementation of the strategy thus is much easier than with the traditional Merton decomposition, as it involves estimating the characteristics of the yield curve and the market prices of risk only, rather than those of numerous (and a priori unknown) state variables. In view of the necessity for optimizing agents to account for the (partial) asset return predictability that derives from the investors’ hedging demands at equilibrium, our result significantly lessens the difficulty of achieving the optimal portfolio strategy. The second hedging term turns out to depend on interest rate differentials across countries and to encompass hedging against PPP deviations. Therefore, in contrast with previous models that obtained a (direct) currency risk hedging component in a rather ad hoc manner, our decomposition leads to optimal (indirect) currency risk hedging in a natural and general way. It also provides new insights as to the pricing of foreign exchange risk at equilibrium.